(3ebOeI aj GdJNWjW GdJfehj GdEbdjej (B/s - (3Zfje, YKeGf eMeOs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 1999)
(3eTcdI GdJNda(B- (3GdJNWjW GdJfehj(B- (3GdJNWjW GdEbdjej(B((3GdfTCI hGdHOGjI(B)- (3GdJNWjW GdEbdjej(B((3Gdeaghe hGdGSGdjH hGdNUGFU(B- (3GdJSdSd GdeQMdj hGdELQGFj dYedjI GdJNWjW GdEbdjej(B- (3fXQjI GdJNWjW GdEbdjej(B- (3GdJLQHI GdCQOfjI(B.s
Keywords: (3GdJNWjW GdJfehjs; (3GdJfejI GdEbJUGOjIs; (3GdJfejI GdEbdjejIs